The Differences between Child Parenting in Germany and Indonesia in Comic as a Cross-Cultural Lecture Material - Hutagalung, Surya M.; Salsabila, Asyifa (Budapest International Research and Critics University, 2021)
The aim of this study is to create comics as a learning media with the topic of the differences in raising children in Germany and Indonesia. This study is a development study. The process of making comics as a learning media consists of explaining the phases of ADDIE theory. These include 1.) analysis, 2.) design, 3.) development, 4.) implementation, 5.) evaluation. The data sources for the material of the comic are based on the results of the interviews with alumni of the German department who participate in Germany's AuPair program. This research is carried out in the Digital Library at Universitas negeri Medan. Based on the results of the interview, five titles are collected. These are â€œresponsibilityâ€, â€œtelevisionâ€, â€œand a day in kindergartenâ€, â€œnew habitsâ€, â€œand tiresome activityâ€. The results of this research are comics in the form of a book with exercises on the theme of history. The comic consists of 24 pages. The comic has been validated by materials experts and media experts. Experts rate that comics are very good as a learning medium for intercultural communication.